Exploring Factors and Impacts of Online Lending on UMKM Expansion in North Sulawesi - Haris, Chadijah (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2024)
This study examines Micro, Small, and Medium Enterprises' (UMKM) perceptions of online loans, employing a descriptive qualitative approach. The research draws upon theoretical frameworks surrounding perception and financial behavior to analyze how UMKM players perceive online loans for business development. Findings indicate that while UMKM players perceive online loans as additional capital facilitating business expansion, there exists a gap in their comprehension of associated risks, notably concerning high-interest rates and over-indebtedness. Consequently, the study emphasizes the critical role of financial education in mitigating these risks effectively. By elucidating the theoretical underpinnings guiding the analysis, this research offers valuable insights into UMKM perceptions of online loans and underscores the importance of educational interventions in enhancing their financial literacy and risk management capabilities. This study contributes to the existing literature by providing a nuanced understanding of UMKM attitudes towards online loans and advocating for comprehensive educational strategies to empower UMKM in navigating the complexities of financial decision-making.